Cote d'Ivoire : Fifth Reviews Under the Arrangement the Extended Credit Facility and Under the Extended Arrangement Under the Extended Fund Facility- Press Release; Staff Report; Supplementary Information and Statement by the Executive Director for Cote d'Ivoire. (IMF Staff Country Reports; Country Report, 2019)
The political context has become more complex and uncertain ahead of the 2020 presidential elections, with the three traditional parties openly competing since the end of the ruling coalition between President Ouattara's Republican Democratic Rally and former President Bedie's Democratic Party of Cote d'Ivoire. Positive investor perceptions of Cote d'Ivoire have so far not been affected. The growth outlook remains strong at 7 1\2 percent, predicated on a continuously improving business environment, buoyant investment and sustained private consumption. Inflation is expected to remain low. Downside risks include the effects of the uncertain political landscape and weaker-than-expected global growth.